Aryl-tetralin-type lignan isolated from Sanguisorba officinalis. Issue 10 (3rd October 2019) - Wang, Li-Na; Qin, Ling-Ling; He, Jun-Lin; Li, Xiao-Hua; Cao, Zhi-Xing; Gu, Yu-Cheng; Deng, Fang; Deng, Yun
Abstract: Three aryl-tetralin-type lignans, including 2 previously undescribed compounds, were isolated from the root of Sanguisorba officinalis . The structures of the new compounds were elucidated by 1D- and 2D-NMR spectroscopic analyses and mass spectrometry. Experimental and calculated ECD were used to determine the absolute configurations. The isolated compounds were evaluated for cytotoxicity against two cell lines (MV4-11 and MDA-MB-231) and compound1 exhibited moderate growth inhibition against MDA-MB-231 cell line with IC50 value of 15.76 μM. Abstract :